Morganella morganii, an Emerging Cause of Bloodstream Infections - Kevin B. Laupland; David L. Paterson; Felicity Edwards; Adam G. Stewart; Patrick N. A. Harris (Microbiology Spectrum, 2022)
ABSTRACT Although recent reports of extensively antibiotic-resistant strains have highlighted the importance of Morganella morganii as an emerging pathogen, the epidemiology of serious infections due to this organism is not well defined. The objective of this study was to determine the incidence, determinants, and outcomes of Morganella morganii bloodstream infections (BSIs). Retrospective, population-based surveillance for Morganella morganii BSIs was conducted in Queensland, Australia, in 2000 to 2019; 709 cases were identified, for an annual incidence of 9.2 cases per million population. Most cases were of community onset, with 280 (39.5%) community-associated cases and 226 (31.9%) health care-associated cases. Morganella morganii BSIs were rare in children and young adults, and the incidence increased markedly with advancing age. The most common foci of infection were skin and soft tissue (131 cases [18.5%]), genitourinary (97 cases [13.7%]), and intraabdominal (90 cases [12.7%]). Most patients (580 cases [81.8%]) had at least one comorbid medical illness, with diabetes mellitus (250 cases [35.3%]), renal disease (208 cases [29.3%]), and congestive heart failure (167 cases [23.6%]) being most prevalent. Resistance to one or more of quinolones, co-trimoxazole, aminoglycosides, or carbapenems was observed in 67 cases (9.5%), and this did not change significantly over the study. The 30-day all-cause case fatality rate was 21.2%, and increasing age, nonfocal infection, heart failure, dementia, and cancer were independently associated with increased risk of death. Morganella morganii BSIs are increasing in our population, and elderly male subjects and individuals with comorbidities are at highest risk. Although antibiotic resistance is not a major contributor to the current burden in Queensland, ongoing surveillance is warranted. IMPORTANCE Recent reports of extensively antibiotic-resistant strains have highlighted the importance of Morganella morganii as an emerging pathogen. Despite its present and evolving importance as an agent of human disease, there is a limited body of literature detailing the epidemiology of serious infections due to Morganella morganii. Therefore, the objectives of this study were to examine the incidence and determinants of Morganella morganii BSIs and to examine risk factors for death in a large Australian population in 2000 to 2019.